Homann Stagnation Point Flow and Heat Transfer of Hybrid Nanofluids Over a Permeable Radially Stretching/Shrinking Sheet - Kho, Yap Bing; Rahimah, Jusoh; Mohd Zuki, Salleh; Mohd Hisyam, Mohd Ariff; Pop, Ioan (Akademi Baru, 2021)
The steady two-dimensional Homan stagnation point flow and heat transfer of water base hybrid nanofluids (Al2O3 & Cu) over a permeable radially stretching/shrinking sheet have been studied. The similarity variables are introduced to transform the partial differential equations of the model into the ordinary differential equations. Numerical findings and dual solutions have been carried out by implementing the bvp4c code through MATLAB software. The most prominent effect is illustrated in the boundary layer thickness where the velocity profile increases upon the increment of the suction intensity but decreases in the temperature profile. Besides, the reduced Nusselt number also decreases as enlarging the value of copper and alumina nanoparticle volume fraction. The analysis of the first and second solutions are presented graphically with critical values as well as the detail discussions on the effects of the other involving parameters.